Fixed-time insemination of suckled beef cows. 2. Cosynch and progesterone - G.C. Lamb; J.A. Cartmill; B.A. Hensley; T.J. Marple; Jeffrey S. Stevenson (Kansas Agricultural Experiment Station Research Reports, 1999)
The Cosynch protocol (GnRH 7 days before and again 48 h after PGF2" with AI at the second GnRH injection) produced pregnancy rates in suckled beef cows that exceeded 50% without heat detection and with only three handlings of all cows. The addition of an intravaginal progesterone insert to the Cosynch protocol improved pregnancy rates in two of the three breeds of cows studied.
Keywords: Cattlemen& #x27; s Day; 1999; Kansas Agricultural Experiment Station contribution; no. 99-339-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 831; Beef; Cows; AI; Estrus-ovulation synchronization; GnRH; PGF2